Indonesian-Version of the Micro, Small & Medium Enterprises with Layth Matthews During His Visit in IPMI Institute - Iqbal Surya; Samuel PD Anantadjaya; Irma M Nawangwulan; Timotius A Rachmat; DC Ethan Samuel; Daniella CE Samuel (Institut IPMI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute the backbone of Indonesia’s economy, representing 99% of all business units and contributing more than 60% to national gross domestic product. Despite their pivotal role in fostering inclusive growth and employment, MSMEs continue to face systemic challenges, including limited access to finance, uneven digital adoption, branding difficulties, and managerial capacity gaps. Addressing these issues requires collaborative interventions that integrate practical business support with academic insights. This manuscript reports on a community service program conducted by IPMI Institute in collaboration with Dr. Layth Matthews, a global expert in leadership, financial literacy, and mindful decision-making. The program, held on August 5, 2025, combined knowledge-sharing sessions with a structured Focus Group Discussion (FGD) involving MSME practitioners, faculty members, and students. Qualitative data were analyzed using NVivo software, employing thematic coding and case classification to capture stakeholder perspectives and identify strategic pathways for MSME empowerment. Findings reveal divergent priorities across stakeholder groups: MSME practitioners emphasized operational challenges such as financing, digitalization, and branding, while lecturers highlighted curriculum integration, applied research, and service-learning as strategic contributions. Convergence was observed in areas of managerial capacity building, mentorship programs, and collaborative forums, underscoring the potential for multi-stakeholder partnerships. The integration of global perspectives situates Indonesia’s MSME challenges within broader emerging economy discourse, highlighting common structural barriers while recognizing Indonesia’s distinctive socio-cultural and geographic context. The study concludes that academic institutions play a critical role in bridging theory and practice, fostering MSME resilience through knowledge transfer, applied research, and community engagement. Recommendations include embedding MSME issues into curricula, expanding mentorship initiatives, and institutionalizing collaborative platforms such as annual MSME forums. By aligning academic missions with practitioner needs, the IPMI–Layth Matthews collaboration exemplifies how universities can contribute meaningfully to inclusive economic growth and socio-economic transformation in Indonesia.